Aplicativo computacional para avaliação de diferenças nos dados de entrada de estudos de fluxo de potência - Duarte, Jones de Queiroz (2007)
Power flow study, also known as load flow, is one of the most important in the power system analysis. In fact, its correct implementation serves as a base for the guarantee of quality, reliability, sustainability and operational security of electric power systems. However, its results may not always be regarded as valid, as a result of various sources of inaccuracies which the power flow methods are subject. In this context, taking into account the existence of these sources on the power flow problem takes on vital importance since, with the knowledge of the uncertainties and approximations involved, can be assessed the degree of adequacy of the power flow analysis. One of the main causes of the deviations that can negatively influence the power flow analysis is in the use of simplified methods for the problem resolution. But even before performed the analysis of flow, the study may be at risk because of distortions in the data that make up the power system. Such discrepancies may originate in the topology, in the parameters or in the operational adjustments of the network. In this Dissertation are reviewed ways of identifying discrepancies from data entry of power flow programs. It also established the analysis of the inaccuracies imposed in the flow calculation by the use of the approximate method known as DC Power Flow. For this method, used mainly when the low computational requirement and the speed of resolution are key variables, it is assessed its suitability for the active power flow analysis of the Brazilian National Interconnected System (SIN).